posted by Rachelle .
I am expected to use the quadratic equation for the following: x2 + 3x – 4 = (x + 4)(x – 1) = 0. Once this is plugged into the value of x (the long equation, which I am unable to copy from the internet, but it goes -3 plus or minus the square root of...) I got
-8/2, but I am also supposed to get 2/2. How do you get 2/2? Thanks!!
The factored equation tells you right way that the answers are -4 and 1.
Apparently, they also want you to derive that result using the quadratic equation
x = [-b +/-sqrt(b^2-4ac)]/2a
= -3 +/-sqrt(9+16)]/2 =
= (-3 +/-(5)/2 = 2/2 or -8/2 = 1 or -4
What you plug into "the long equation" is the values of a, b and c in the polynomial, NOT x.